2013
DOI: 10.1073/pnas.1302933110
|View full text |Cite
|
Sign up to set email alerts
|

Essential roles of grp94 in gut homeostasis via chaperoning canonical Wnt pathway

Abstract: Increasing evidence points to a role for the protein quality control in the endoplasmic reticulum (ER) in maintaining intestinal homeostasis. However, the specific role for general ER chaperones in this process remains unknown. Herein, we report that a major ER heat shock protein grp94 interacts with MesD, a critical chaperone for the Wnt coreceptor low-density lipoprotein receptor-related protein 6 (LRP6). Without grp94, LRP6 fails to export from the ER to the cell surface, resulting in a profound loss of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
109
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(115 citation statements)
references
References 41 publications
3
109
0
1
Order By: Relevance
“…Clinically, gp96 expression correlates with advanced stage and poor survival in a variety of cancers and is closely linked to cancer growth and metastasis in melanoma, breast, prostate, multiple myeloma, lung cancer, and colon cancer (22- 29). gp96 has also been found to confer decreased sensitivity to x-ray irradiation (30), and it is required for the canonical Wnt pathway (31). Recently, our group showed that the maturation of a majority of integrins is dependent on gp96, which folds integrins in the ER and controls their surface expression (32)(33)(34).…”
mentioning
confidence: 99%
“…Clinically, gp96 expression correlates with advanced stage and poor survival in a variety of cancers and is closely linked to cancer growth and metastasis in melanoma, breast, prostate, multiple myeloma, lung cancer, and colon cancer (22- 29). gp96 has also been found to confer decreased sensitivity to x-ray irradiation (30), and it is required for the canonical Wnt pathway (31). Recently, our group showed that the maturation of a majority of integrins is dependent on gp96, which folds integrins in the ER and controls their surface expression (32)(33)(34).…”
mentioning
confidence: 99%
“…LRP6/GRP complex 1C) and slightly reduced the level of LRP6 (Fig. 1B), which is dependent on GRP94 for its cell-surface expression (29). In contrast, 3 mmol/L of TAS-116 did not markedly affect the LRP6-GRP94 interaction.…”
Section: Tas-116 Selectively Inhibits Hsp90a and Bmentioning
confidence: 87%
“…Recently, it was discovered that GRP94, a critical chaperone for the Wnt coreceptor LRP6, has a functional role in gut homeostasis via regulation of the canonical Wnt signaling pathway (29). Conditional deletion of grp94 results in rapid weight loss, diarrhea, and hematochezia in mice that are characterized by a gut-intrinsic defect in the proliferation of intestinal crypts, as well as compromised nuclear b-catenin translocation, loss of crypt-villus structure, and impaired barrier function (29). It however remains unclear whether pharmacologic inhibition of GRP94 would mimic such effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…63 LRP6, in turn, is required for canonical Wnt signaling and functions as a coreceptor for the cell surface Wnt receptor, Frizzled. 69 Genetic deletion of GRP94 attenuates multiple myeloma in a mouse model of the disease. 70 Additionally, silencing GRP94 compromised human multiple myeloma cell growth.…”
mentioning
confidence: 99%